Pengaruh Pengalaman Kerja terhadap Disiplin Kerja Karyawan pada Bank Syariah PT.Bprs Puduarta Insani Tembung - Sulistia ningrum; Alfi Amalia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the influence of work experience on work discipline at the Sharia Bank PT. BPRS Puduarta Insani Tembung, both partially and simultaneously. This research approach is associative. The population is all employees and the sample is 19 employees. Data collection techniques in this research used interview techniques, documentation studies, observations and questionnaires. The data analysis technique in this research uses Multiple Linear Regression Analysis Test, Hypothesis Test (t Test and F Test), and Coefficient of Determination. Data processing in this research used the SPSS (Statistical Package for the Social Sciences) software program version 29.00. Partially, the work experience variable has a significant effect on work discipline at the Sharia Bank PT. BPRS Puduarta Insani Tembung. Simultaneously, the work experience variable has a significant effect on work discipline at Bank Syariah PT. BPRS Puduarta Insani Tembung.